How Well Do Couples Care When They Are Expecting Their First Child? Family and Dyadic Predictors of Parental Sensitivity in Expectant Couples - Kaźmierczak, Maria; Pawlicka, Paulina; Łada-Maśko, Ariadna B.; van IJzendoorn, Marinus H.; Bakermans-Kranenburg, Marian J. (Frontiers in Psychiatry, 2020)
The Belsky’s process model points to family-of-origin (especially experiences of mistreatment in childhood), as well as personality and marital relations as determinants of parenting quality, including parental sensitive responsiveness. Parental sensitivity might be intuitively developed during pregnancy and affects perinatal mental health. However, there’s a lack of studies investigating effects of family-of-origin and relationship perceptions on expectant couples’ parental sensitive responsiveness. The aim of the presented study was to test mediation and moderation effects of perceived partner’s empathic concern and retrospectively assessed abuse experienced in childhood on sensitive parental responsiveness operationalized as caretaking behaviors and emotional reactions to a crying life-like doll. One hundred and eleven expectant couples (N = 222; age: Mwomen = 28.4, SD = 3.03; Mmen= 29.2, SD = 3.31; relationship duration Myears= 6.8, SD = 3.43; gestational week: M = 31.3, SD= 4.58) assessed the extent to which their experienced physical and emotional abuse from their parents in childhood and rated their current partner’s empathic concern. In the experimental procedure couples reacted to a crying life-like doll and were assessed by trained psychologists with the modified Ainsworth Sensitivity Scale to measure couples’ sensitive responsiveness. The results confirmed a significant mediational effect of perceived women’s (and not men’s) empathic concern for the relationship between abuse in family-of-origin experienced by expectant fathers (and not mothers) and couples’ sensitivity. Support and interventions regarding couples’ empathy and parenting competences can be offered to both mothers and fathers to identify those who are at risk of low parental sensitivity..